Watershed Management For Cheney Reservoir to Protect a Drinking Water Source - Powell, G. Morgan (My University, 1999)
This publication describes watershed management and uses the N.F. Ninnescah Watershed as an example.
MF2397_1999-07.pdf
Keywords: MF2397; Environment and Natural Resources; Health and Safety; MF